Bond characteristics of straight- and headed-end, ribbed-surface, GFRP bars embedded in high-strength concrete. (15th May 2015) - Islam, Sirajul; Afefy, Hamdy M.; Sennah, Khaled; Azimi, Hossein
Highlights: Bond characteristics of both straight- and headed-end GFRP bars are studied experimentally. 180 pullout tests were conducted to cover 30 parameters. Empirical equation is proposed for the development length calculation of GFRP bars. Development lengths based on experimental results are compared with the available design standards. CSA S6-06 showed the closest development length results to the experimental findings. Abstract: Glass Fiber Reinforced Polymer (GFRP) bars as a proper substitute for traditional reinforcing steel bars not only eliminate the durability problem due to corrosion of reinforcing steel, but also provide remarkably enhanced capacity due to their high tensile strength compared to that of the steel bars. This paper presents the experimental findings of 180 pullout tests conducted on GFRP bars embedded into high-strength concrete blocks covering different parameters. The studied parameters were bar diameter size (12 or 16 mm), embedment length (4 or 6 times the bar diameter), bar end condition (straight and headed), and concrete cover (1.5, 2.5, and 5 or 7 times bar diameter for straight bars and 8 or 10.5 times bar diameter for headed bars) in addition to a case of no embedment length except the head length for headed-end bars. In total, 30 variables were studied, while each variable was conducted on 6 identical specimens in order to increase the reliability of the results. Based on the results of the parametric study, the bond stress was shown to be inversely proportional to the embedment length and bar diameter as expected. In addition, the smaller concrete cover appeared to have significant effect on bond stress, leading to side blow-out failure rather than bar pullout or concrete splitting in the case of headed-end GFRP bars. In addition, the GFRP bar with headed-end showed significant increase in pullout strength compared to that for the straight-end bars. Finally, an empirical expression was proposed to calculate the development length of GFRP bars with either straight or headed-end, and then compared with the available design standards such as CSA-S806-02, CSA S6-06, ACI 440-1R-06, and JSCE-97. The comparison showed that the results developed by CSA S6-06 standards was the closest to the experimental findings showed about 2% safety margin exceeding the obtained development length by the proposed expression.